Rescue for an advanced aging patient with synchronous AOSC and gallstone ileus: a case report and literature review - Wu, Junhui; Lu, Jun; Jia, Zhong (Frontiers in Surgery, 2025)
BackgroundCholecystolithiasis is the most common disease of the gallbladder. Both acute obstructive suppurative cholangitis (AOSC) and gallstone ileus are critical clinical conditions requiring urgent intervention. However, their synchronous occurrence, particularly in elderly patients, presents a significant therapeutic challenge. In such scenarios, an optimal treatment strategy is essential to ensure patient safety while minimizing procedural risks.Case presentationHerein, we described a 91-year-old women with cholecystolithiasis who was admitted for a day of abdominal pain accompanied by jaundice and fever. Upon admission, the patient was hemodynamically instable, and blood tests showed elevated white blood cell count and severe liver dysfunction. Emergency computed tomography (CT) revealed intra- and extra-hepatic bile duct dilation with pneumobilia, sludge-like stone at the distal common bile duct (CBD), a cholecystogastric fistula, and a gallstone within the gastric lumen. Soon after, the patient suffered from periumbilical pain. Re-evaluation CT showed the gastric gallstone had migrated into the intestinal lumen, causing gallstone ileus. We first performed ultrasound-guided percutaneous transhepatic cholangial drainage. Three days later, the symptoms resolved. We subsequently performed a curative surgery, including enterolithotomy, cholecystectomy, CBD exploration, and fistula closure. After surgery, the patient recovered successfully. At 3 months of follow-up, she resumed daily activities, with no adverse events.ConclusionsSynchronous AOSC and gallstone ileus can be life-threatening; however, AOSC carries a higher mortality risk and should be addressed as the immediate priority. In hemodynamically unstable patients, particularly the elderly, extensive surgery should be avoided in the acute phase to reduce perioperative risk. Once stabilized, enterolithotomy and definitive repair can be performed to achieve a favorable outcome.